Evaluation of blood product transfusion therapies in acute injury care in low- and middle-income countries: a systematic review. Issue 7 (July 2020) - Yang, Lanbo; Slate-Romano, John; Marqués, Catalina González; Uwamahoro, Chantal; Twagirumukiza, Francois Regis; Naganathan, Sonya; Moretti, Katelyn; Jing, Ling; Levine, Adam C.; Stephen, Andrew; Aluisio, Adam R.
Highlights: Low- and middle-income countries (LMICs) experience disproportionately high mortality burdens due to injuries. To date, no international or society derived standards or guidelines exist for the use of blood product transfusion therapies in LMICs, and the available data from LMIC settings have not been evaluated previously. There are limited high-quality data from LMICs on blood product transfusion therapies in injury care, with deficiencies in the available data pertaining to geographic settings, types of therapies and usage in specific injury patterns. Future research is needed to enhance understanding of and promote guideline development for the appropriate, safe and most effective use of blood product transfusion therapies for injuries in LMICs. Abstract: Background: Worldwide, injuries account for approximately five million mortalities annually, with 90% occurring in low- and middle-income countries (LMICs). Although guidelines characterizing data for blood product transfusion in injury resuscitation have been established for high-income countries (HICs), no such information on use of blood products in LMICs exists. This systematic review evaluated the available literature on the use and associated outcomes of blood product transfusion therapies in LMICs for acute care of patients with injuries. Methods: A systematic search of PubMed, EMBASE, Global Health, CINAHL and Cochrane databases through November 2018 was performed by a health sciences medical librarian. Prospective and cross-sectional reports of injured patients from LMICs involving data on blood product transfusion therapies were included. Two reviewers identified eligible records (κ=0.92); quality was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Report elements, patient characteristics, injury information, blood transfusion therapies provided and mortality outcomes were extracted and analyzed. Results: Of 3411 records, 150 full-text reports were reviewed and 17 met inclusion criteria. Identified reports came from the World Health Organization regions of Africa, the Eastern Mediterranean, and South-East Asia. A total of 6535 patients were studied, with the majority from exclusively inpatient hospital settings (52.9%). Data on transfusion therapies demonstrated that packed red blood cells were given to 27.0% of patients, fresh frozen plasma to 13.8%, and unspecified product types to 50.1%. Among patients with blunt and penetrating injuries, 5.8% and 15.7% were treated with blood product transfusions, respectively. Four reports provided data on comparative mortality outcomes, of which two found higher mortality in blood transfusion-treated patients than in untreated patients at 17.4% and 30.4%. The overall quality of evidence was either low (52.9%) or very low (41.2%), with one report of moderate quality by GRADE criteria. Conclusion: There is a paucity of high-quality data to inform appropriate use of blood transfusion therapies in LMIC injury care. Studies were geographically limited and did not include sufficient data on types of therapies and specific injury patterns treated. Future research in more diverse LMIC settings with improved data collection methods is needed to inform injury care globally.